NEUROEKONOMI & TRUST PADA MENTALITAS ENTREPRENEUR MUSLIM DI KOTA PEKALONGAN - Susminingsih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
This research explains that among the Muslim entrepreneur of Pekalongan City, the role of trust as an output of neuro-economic process has taken a part in forming their entrepreneur mentality. The dimension of their entrepreneur mentality includes their commitment to business (commitment to chance, sources, and appearing risk), creative behavior (thinking new thing and doing new thing or create the new and different thing), confidence, responsibility, and positive thinking. This research used qualitative approach based on post-positivistic paradigm, and symbolic interactionism theory to explain. Content analysis-philosophy was used to analyze the answers of interviewee, so that the result of this research is philosophical-analytical-holistic.